Adenovirus Genotype 7 Detection in Adults with Respiratory Infection and Elevated IL-6: Deteksi Genotipe Adenovirus 7 pada Dewasa dengan Infeksi Pernafasan dan Kadar IL-6 yang Tinggi - Ahmed Tofiq, Wirya; Saadoon, Israa Hashim (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): Human adenoviruses are widespread pathogens responsible for a significant proportion of respiratory tract infections, with genotype 7 (HAdV-7) associated with severe outcomes. Background (Specific): Despite its clinical importance, limited data exist regarding the prevalence and immunological impact of HAdV-7 among adult patients in Iraq. Knowledge Gap: The relationship between HAdV-7 infection and interleukin-6 (IL-6) levels in adults with respiratory illness has not been well characterized. Aim: This study aimed to detect HAdV-7 in adult patients with respiratory infections using RT-PCR and to evaluate its association with IL-6 levels. Results: Among 100 patients and 50 healthy controls, HAdV-7 was detected in 7% of cases, with no significant association with age, sex, or residence. Patients infected with HAdV-7 exhibited significantly elevated IL-6 levels (101.75 ± 25.17 pg/mL) compared with controls (39.26 ± 11.09 pg/mL, p ≤ 0.05). Novelty: This is one of the first molecular investigations in Iraq to link HAdV-7 infection with heightened IL-6 responses, highlighting the virus’s role in driving inflammatory pathways. Implications: Monitoring IL-6 levels may serve as a biomarker for disease severity in HAdV-7 infections and support timely therapeutic interventions to reduce complications.Highlight : HAdV-7 detection by RT-PCR shows its link with increased IL-6 levels. Molecular methods enhance sensitivity for early diagnosis. IL-6 monitoring can guide prognosis and therapy. Keywords : ELISA, RT-PCR, HAdV, Respiratory Infection, IL-6